Garment printing methods and print types used by selected printing companies - Gacutan, Ann Therese M.
The aesthetics of many embellished fabrics are governed by the type of image, pattern or print that has been applied to their surface. Prints are very important factors in choosing a garment. It is the element that gives an attitude and a certain image to the fabric or a certain piece of clothing. The main objective of the study was to identify the garment printing methods and print types used by selected garment printing companies in Metro Manila. Specifically it sought to determine the fabric compatibility of each print type and the common problems encountered in garment printing. Since there has not been any study conducted in the College of Home Economics, Clothing Textile and Interior Design Department on garment printing, this study will provide significant information concerning garment printing. This is a descriptive research. The principal data-gathering methods that were used in this study were guided questionnaire, interview and plant visits with the local garment printers. A total of nine printers were randomly selected to be the respondents of this study. Observational and documentary research have also been conducted prior to the administration of the interview and plant visits to gather preliminary data on garment printing. The focus of the interview and plant visit was to gather vital information on garment printing, namely- the limitation and uniqueness of each print type, its pricing and fabric compatibility, the machines and materials involved and the common problems encountered. Visual presentation of the gathered data was used to effectively show the methods and print types. The results showed that screen, adhesive, air-brush and heat transfer printing are the garment printing methods used by selected printers in Metro Manila. It was found that there were different types of prints under screen and adhesive printing. Majority of the respondents said that water-based screen-printing was the most common print used in garments. Fabric compatibility was one of the main factors affecting the quality of the print. The results showed that most prints are compatible with cotton and cotton-polyester and incompatible with spandex and silk. The data gathered revealed that bleeding and cracking were the most common problems encountered in garment printing.